"Eorlas arhwate eard begeatan" revisiting Brunanburh's (hi)story, style and imagery in translation - Bueno Alonso, Jorge Luis (Babel: Revue Internationale de la Traduction = International Journal of Translation, 2011)
The poetic insert known as The Battle of Brunanburh (Anglo-Saxon Chronicle 937) constitutes by no means one of the most interesting texts for the building of the Old English heroic geography. Its author, as Marsden states (2005: 86), “builds a sense of national destiny, using style, diction and imagery of heroic poetry”. There are many interesting issues to deal with when you want to revise how the elements Marsden quotes are used in the construction of a poem that uses history as a narrative device to build the inner story of the poem experimenting with the topics (style, diction, imagery) of heroic poetry. If the poem constitutes such a crucial text, if its emphasis is on “English nationalism” in an historical perspective rather than on individual heroics, as Marsden points out (2005: 86), it seems most evident that a careful consideration of these topics has to be made when translating the text into other languages. The aim of this article is to revisit the poem and its topics and to see how that careful consideration has been accomplished in several important English (Treharne 2004, Hamer 1970, Rodrigues 1996, Garmonsway 1953, Swanton 2000) and Spanish (Lerate & Lerate 2000, Bravo 1998, Bueno 2007) translations that consider the poem in isolation, in the context of the Anglo-Saxon Chronicle or as an excuse for poetic inspiration, i.e. the case of Borges’ 1964 and 1975 poems and Tennyson’s 1880 text.